1-(3-Amino-1-benzofuran-2-y1)-2-mesityl-ethanone - Arici, C; Ülkü, D; Kirilmis, C; Koca, M; Ahmedzade, M (Int Union Crystallography, 2004)
The title compound, C19H19NO2, features a benzofuran ring system coplanar with an amino substituent and linked to a mesityl group by an acetyl bridge. In the crystal structure, symmetry-related molecules are linked by N-H...O intermolecular hydrogen bonds involving one amino H atom and the O atom of the acetyl group to form infinite chains. The other amino H atom is involved in an intramolecular hydrogen bond with the acetyl O atom.